Assessing PT Mustika Ratu's Performance: A Balanced Scorecard Measurement: Evaluasi Kinerja PT Mustika Ratu: Pengukuran dengan Balanced Scorecard - Sugiyanti, Sherlina; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2025)
General Background The intense global business competition necessitates comprehensive performance measurement beyond mere financial data to ensure sustainable corporate strategy implementation. Specific Background PT Mustika Ratu Tbk., a long-standing Indonesian cosmetics and herbal company, faces tight competition which led to fluctuating performance between 2019 and 2022, requiring a holistic performance evaluation. Knowledge Gap While the Balanced Scorecard (BSC) is a recognized method, its application and specific findings on performance dynamics within the Indonesian traditional-to-modern cosmetic industry, especially post-pandemic, remain an area for detailed analysis. Aims This study aimed to analyze and understand the performance of PT Mustika Ratu Tbk. during 2019–2022 using the four perspectives of the BSC (Financial, Customer, Internal Business, and Learning & Growth). Results Overall performance was assessed as moderately good. The Financial perspective showed fluctuating but increasing profitability (ROA); Customer profitability increased; Internal Business Process efficiency was good despite a pandemic dip; but Learning and Growth (employee productivity) remained unstable. Novelty This research provides up-to-date, quantitative-descriptive insights into a key player in Indonesia's beauty sector over a four-year period, offering a specific diagnostic tool for management strategy. Implications The findings emphasize the need for managerial strategies to stabilize employee productivity and optimize asset utilization for sustained growth. Highlights: Overall corporate performance is moderately good based on four BSC perspectives. Financial results show fluctuating ROA but a trend of profit increase. Employee productivity in the learning and growth perspective remains unstable. Keywords: Balanced Scorecard, Performance Measurement, PT Mustika Ratu, Financial Analysis, Employee Productivity